2013
DOI: 10.4028/www.scientific.net/kem.594-595.691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Treatment on the Mechanical Properties of Pultruded Kenaf Fibre Reinforced Polyester Composites

Abstract: In this study, Pultruded Kenaf Reinforced Composites (PKRC) has been successfully produced using pultrusion technique. The chemical treatment using sodium hydroxide (NaOH) at different concentration (3%, 6% and 9% M) were carried out to modify the fibre properties. After successfully characterized, it was found that kenaf fibre treated with 6% NaOH recorded the best improvement in term of mechanical properties. In particular, treated pultruded kenaf reinforced composites (TPKRC) shows better tensile and flexur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Surface modification has been made for better interfacial bonding between natural fibers and the matrix. A good interfacial bond prompts better load transfer and thus better properties .…”
Section: Introductionsupporting
confidence: 85%
“…Surface modification has been made for better interfacial bonding between natural fibers and the matrix. A good interfacial bond prompts better load transfer and thus better properties .…”
Section: Introductionsupporting
confidence: 85%
“…Actually, kenaf-reinforced composites have used a diversified number of polymer matrices including PP [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], polyester [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], polyurethane [ 37 , 38 ], high-density polyethylene [ 22 , 39 , 40 , 41 ], polystyrene [ 42 ], polylactic acid [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], natural rubber [ 52 ], PVC [ 53 ], and epoxy [ 54 ] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Bin Saiman et al 92 focused on the effect of alkali treatment (6% NaOH) of woven kenaf on impact strength of the UPE composites prepared by vacuum infusion process, where the alkali treatment improved the impact strength of the composites. Osman et al 93 also found that kenaf fiber treated with 6% NaOH recorded the best improvement in term of mechanical properties. The results showed that alkali treatment enhanced the impact strength of the composites compared to neat polyester and untreated composite.…”
Section: Properties Of the Composites Produced Using Treated Kenaf Fibermentioning
confidence: 92%
“…Many studies have been reported on the use of alkaline treatment for kenaf fibers. 29,83,[90][91][92][93][94][95][96][97] The treatment using NaOH has been found to be an effective approach to remove the impurities on the surface of kenaf fiber. 29 Asim et al 29 treated kenaf fiber with 6% NaOH (w/v) and showed via FTIR analysis that alkaline treatment reduces the intensity of typical peaks of lignin and hemicellulose.…”
Section: Properties Of the Composites Produced Using Treated Kenaf Fibermentioning
confidence: 99%